Training Package for Developing Teacher’s Skill in Creating Classroom Management Activity for Reducing Students’Misbehavior in Oob-om Kindergarten School, Satun Province - Madyed, Haslinda (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI: 10.14456/pnuhuso.2023.4 The objectives of this research were to 1) develop teachers’ skills in creating classroom management activity packages, 2) evaluate skills in creating classroom management activity packages, and 3) study teacher satisfaction towards teacher skill development. in creating a set of activities.This research was used as a quasi-experimental research by selecting a sampling group of 6 teachers. The tools used for data collection were the teacher skills training package for creating the activity package. Assessment form for teacher’s activity-building skills after training with the training package and a questionnaire on teacher satisfaction towards the training package. Data were analyzed using descriptive statistics consisting of percentage, mean and standard deviation. The study results were as follows: 1) The efficiency of developing teachers’ skills in creating classroom management activities according to the specified criteria was 82.88/81.83. and 3) the teacher’s satisfaction with the training package was at a high level.